Glide-Symmetric Fully Metallic Luneburg Lens for 5G Communications at Ka-Band - Quevedo-Teruel, Oscar; Miao, Jingwei; Mattsson, Martin; Algaba-Brazalez, Astrid; Johansson, Martin; Manholm, Lars (IEEE antennas and wireless propagation letters, 2018)
Here, we propose a fully metallic implementation of a Luneburg lens operating at Ka-band with potential use for 5G communications. The lens is implemented with a parallel plate that is loaded with glide-symmetric holes. These holes are employed to produce the required equivalent refractive index profile of a Lune-burg lens. Glide symmetry and inner metallic pins are employed to increase the equivalent refractive index. The lens is fed with rectangular waveguides designed to match the height of the parallel plate, and it is ended with a flare to minimize the reflections.